Ginsenoside Rg3 targets glycosylation of PD-L1 to enhance anti-tumor immunity in non-small cell lung cancer - Wang, Wei; Kong, Min; Shen, Fu; Li, Ping; Chen, Cheng; Li, Yueqin; Li, Cheng; Qian, Zhiqiang; Zhong, Aihua; Wang, Yuhua; Yang, Liang; He, Fangkai; et al. (Frontiers in Immunology, 2024)
Background Reactivate the T cell immunity by PD-1/PD-L1 checkpoint blockade is widely used in non-small cell lung cancer (NSCLC) patients, while the post-translational modification of Programmed death ligand-1 (PD-L1) is commonly existed in various cancer cells, thus increases the complexity and difficulty in therapy development. Ginsenoside Rg3 is an active component of traditional Chinese herb Ginseng with multiple pharmacological effects including immune regulation. However, the effect on the glycosylation of PD-L1 is unknown. Methods NSCLC cell lines were tested for glycosylation of PD-L1, and the potential mechanisms were investigated. Tumor cell-T cell coculture experiment was conducted and the activation of T cells and cytotoxicity were measured by flow cytometry. In vivo xenograft mouse tumor model was used to investigate the effects of Rg3 on PD-L1-mediated immunosuppression and tumor growth. Results Here, we identified PD-L1 is widely N-linked glycosylated in NSCLC cell lines, while Rg3 could inhibit the glycosylation of PD-L1 by downregulating the EGFR signaling and further activate GSK3b-mediated degradation, thus resulted in reduced PD-L1 expression. Moreover, the inhibition of PD-L1 glycosylation promoted the activation and cytotoxicity of T cells under coculture condition. In addition, Rg3 could decrease the tumor volume and enhance anti-tumor T cell immunity as evidence by the upregulated expression of Granzyme B and perforin in CD8+T cells, along with elevated serum IL-2, IFN-g and TNF-a level in Rg3-treated mice. Conclusions These results suggest that Rg3 inhibits PD-L1 glycosylation and thus enhance anti-tumor immunity, which provide new therapeutic insight into drug discovery.